STRATEGI MENDIDIK GENERASI Z DI ERA DIGITAL PERSPEKTIF TEORI SOSIOLOGI - M. Fauzan; Marta Novika; Muhiddinur Kamal; Hendrisab (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The concept of theory is often understood in various ways, ranging from views that consider it unrealistic to those that see it as impractical. As an effort to interpret social phenomena, theory plays a crucial role in answering the question of "why" related to social conditions. This research aims to explore sociological theories, particularly those relevant to Generation Z, who experience social imbalance due to the influence of technology. The methodology employed is library research, where data is collected through the examination of journals, books, and relevant documents. This study finds that Generation Z, despite being skilled in technology, faces mental health issues such as anxiety and depression exacerbated by the culture of Fear of Missing Out (FOMO) on social media. The tension between traditional values and new norms creates significant social challenges. The findings of this research are expected to provide insights into the importance of sociological theory in understanding the behavior of Generation Z and the impact of technology on their social interactions. Thus, this study emphasizes the need for a theoretical approach to understand and address the issues faced by today's youth.